Mechanisms for change: A theoretical pathway for a school-wide social–emotional learning initiative in an urban middle school - White, Gwyne W.; Hatchimonji, Danielle R.; Vaid, Esha; Simmons, Christopher C.; Yuan, May; Wang, Angela; Elias, Maurice J. (Frontiers in Psychology, 2023)
Investment in academic instruction without complementary attention to the social-emotional environment of students may lead to a failure of both. The current study evaluates a proposed mechanism for change, whereby academic achievement occurs as a result of the social-emotional learning environment impacting behavioral (discipline) outcomes. We tested the hypothesized model during each year of a 3-year intervention to determine whether the relations among these constructs held potential as a pathway for targeted improvement. Path analysis for each year demonstrated excellent fit (Year 1: χ2(19)=76.16, CFI=.99, RMSEA=.05,TLI=.98; Year 2: χ2(19)=70.68, CFI=.99, RMSEA=.048, TLI=.98; Year 3: χ2(19)=66.59, CFI=.99, RMSEA=.05, TLI=.98) supporting the theoretical model for change. For each year the effect of the SEL Environment construct on discipline was significant, as was the effect of discipline on Academic Performance. Further, the indirect effect of SEL Environment on Academic Performance was significant across all years. The consistency of these relationships supports the proposed logic model as a potential mechanism for change and has the potential to guide interventions for whole school improvement.